Pengaruh Kualitas Pelayanan Mobile Banking Terhadap Kepuasan Nasabah Pada Bank Syariah Indonesia (BSI) - Fina Afriliyana; Intan Sri Wahyuni; Abdullah Faursam; Henny Saraswati; Wahyu Hidayat (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to find out whether mobile banking service quality has a significant effect on customer satisfaction and whether security using mobile banking has a significant effect on customer satisfaction. Furthermore, this study also aims to determine whether accuracy and trust have a significant effect on customer satisfaction. This type of research is quantitative research using research surveys. The sample of this research is 30 respondents taken by survey method. Data collection techniques using questionnaires and surveys. Methods of data analysis using linear regression test, normality test, hypothesis testing, correlation test (T test, F test), then the data is processed using the SPSS application from windows.